Dampak Terapi Seni Ekspresif terhadap Trauma pada Remaja yang Dipenjara - Abrar, Khairunnisa Putri (INSAN Jurnal Psikologi dan Kesehatan Mental, 2024)
This study examines the effectiveness of expressive arts therapy in mitigating childhood trauma in incarcerated youth, with the aim of reducing the risk of mental disorders, violence, and recidivism by identifying and treating underlying trauma. The study involves 12 participants from the incarcerated youth population, 6 in each group; however, one participant in the control group dropped out of the study during the post-test due to non-attendance. The study used a quasi-experimental design. The experimental group received four sessions over a period of one week. The study found no significant reduction in PTSD symptoms using expressive arts therapy, analyzing for time measured (p=0.700), experimental group (p=0.037), and their interaction (p=0.568). This study found that expressive arts therapy did not significantly reduce posttraumatic stress symptoms in incarcerated youth, likely due to several factors. Future studies should address methodological limitations such as nonrandomization and explore alternative therapies.